FROM A SPORTS TEAM TO AN EDUCATIONAL TEAM OF A SPORTS PROFILE (ON THE EXAMPLE OF FENCING) - Lobanov V.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop a definition of the educational team as a new scientific and pedagogical category, to characterize its features and functionality, taking into account the context of the fencing sport. Methods and structure of the study. The research methodology is based on the study of scientific, theoretical and methodological literature, the use of modeling methods, pedagogical and content analysis. The study is based on the identification of modern ideas about the importance of a sports team on the example of fencing programs. Results and conclusions. The article reveals modern scientific and methodological ideas about the educational significance of the team, identified in the process of analyzing the programs of 1998-2022. in the sport of fencing. The insufficient effectiveness of the approach to the organization of personality education in a sports team is substantiated, taking into account the fluidity of the composition, the invariance of values and goals that are external to athletes. The key factors of upbringing (the authority of the coach, traditions, a specialized environment created with the creative participation of students, the practice of mentoring experienced athletes, holding open classes) that create the prerequisites for the formation of a team are identified. In the context of collective activity and education, a definition is introduced into the theory of pedagogy and the functionality of the educational team is described.